Perimeter and Area problem

Algebra Level 2

Let a a be the long side & b b be the short side of a rectangle.

We know that the rectangle's perimeter is 36 ( c m ) 36(cm) and it's area is 77 ( c m 2 ) 77(cm^2)

Find a b \dfrac{a}{b} .


The answer is 1.5714285714285714.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Gia Hoàng Phạm
Sep 21, 2018

a b = 77 , 2 ( a + b ) = 36 a + b = 18 ab=77,2(a+b)=36 \implies a+b=18

We know that a = ( a + b ) + ( a + b ) 2 4 a b 2 , b = ( a + b ) ( a + b ) 2 4 a b 2 a=\frac{(a+b)+\sqrt{(a+b)^2-4ab}}{2},b=\frac{(a+b)-\sqrt{(a+b)^2-4ab}}{2}

So a b = ( a + b ) + ( a + b ) 2 4 a b 2 ( a + b ) + ( a + b ) 2 4 a b 2 = ( a + b ) + ( a + b ) 2 4 a b 2 × 2 ( a b ) + ( a + b ) 2 4 a b = ( a + b ) + ( a + b ) 2 4 a b ( a + b ) ( a + b ) 2 4 a b \frac{a}{b}=\frac{\frac{(a+b)+\sqrt{(a+b)^2-4ab}}{2}}{\frac{(a+b)+\sqrt{(a+b)^2-4ab}}{2}}=\frac{(a+b)+\sqrt{(a+b)^2-4ab}}{2} \times \frac{2}{(a-b)+\sqrt{(a+b)^2-4ab}}=\frac{(a+b)+\sqrt{(a+b)^2-4ab}}{(a+b)-\sqrt{(a+b)^2-4ab}}

So plug in numbers & we got 18 + 1 8 2 4 × 77 18 1 8 2 4 × 77 = 18 + 324 308 18 324 308 = 18 + 4 18 4 = 22 14 = 11 7 1.5714285714285714 \frac{18+\sqrt{18^2-4 \times 77}}{18-\sqrt{18^2-4 \times 77}}=\frac{18+\sqrt{324-308}}{18-\sqrt{324-308}}=\frac{18+4}{18-4}=\frac{22}{14}=\frac{11}{7} \approx \boxed{\large{1.5714285714285714}}

Note

  • a b = ( a + b ) 2 4 a b = a 2 + 2 a b + b 2 4 a b = a 2 2 a b + b 2 = ( a b ) 2 |a-b|=\sqrt{(a+b)^2-4ab}=\sqrt{a^2+2ab+b^2-4ab}=\sqrt{a^2-2ab+b^2}=\sqrt{(a-b)^2}

  • a = ( a + b ) + ( a + b ) 2 4 a b 2 = ( a + b ) + ( a b ) 2 = a + b + a b 2 = 2 a 2 , b = ( a + b ) ( a + b ) 2 4 a b 2 = ( a + b ) ( a b ) 2 = a + b a + b 2 = 2 b 2 a=\frac{(a+b)+\sqrt{(a+b)^2-4ab}}{2}=\frac{(a+b)+(a-b)}{2}=\frac{a+b+a-b}{2}=\frac{2a}{2},b=\frac{(a+b)-\sqrt{(a+b)^2-4ab}}{2}=\frac{(a+b)-(a-b)}{2}=\frac{a+b-a+b}{2}=\frac{2b}{2}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...